Integrated origin-based demand modeling for air transportation. (October 2020) - Birolini, Sebastian; Cattaneo, Mattia; Malighetti, Paolo; Morlotti, Chiara
Highlights: Integrated demand generation and allocation model assuming demand saturation at origin level. Separate modeling by travel lengths highlights different sensitivities to air travel determinants. Air transport supply found to significantly affect destination choice and air trip making. Assessment of newly generated demand and passengers allocation on itineraries and destinations. Abstract: This paper proposes an origin-based air travel demand model that assumes saturation at the origin level and explicitly accounts for substitutability between destinations. We simultaneously integrate demand generation and allocation by means of a multilevel aggregate nested logit formulation that covers the choices of whether or not to travel by air, where to travel (destination), and how to travel (itinerary). Two specifications are proposed to reflect systematic differences between lengths of haul and the bootstrap is applied to jointly address endogeneity issues and data missingness. The validity of the proposed approach is tested over the entire network of outbound air trips from Italy in 2018.